Restorative Justice at The Investigation Stage of Victimless Crimes - Nur Fadillah, Astuti; Corputty, Patrick (Jurnal Cakrawala Hukum, 2025)
Victimless crime is a crime that places the perpetrator of the crime as a victim, so that in efforts to overcome crime, the term restorative justice is used, namely a model for resolving criminal acts that prioritizes victim recovery. The problem that occurs is the basis of norms in law enforcement officers using restorative justice in efforts to overcome victimless crime, pornography crimes are one type of cybercrime. In the current era of globalization, Indonesia is facing the problem of pornography because the rampant spread of pornography on the internet has had an impact on the social life of society and is still considered normal by some people. The method used in this study is the socio-legal research method. Where this study looks at how the police use a restorative approach in efforts to overcome crime, especially victimless crime. There are several types of victimless crime that are highlighted in this study, including gambling crimes, drug abuse crimes and pornography crimes. The results of this study indicate that investigators have not been optimal in using restorative justice in handling victimless crime crimes.